2013
DOI: 10.1007/s11695-013-1041-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-Incision Laparoscopic Cholecystectomy and Overweight Patients

Abstract: This retrospective study comparing overweight and normal weight patient in SILC demonstrates that SILC is associated with the prolonged operative time, high additional port requirement, and increased wound complication rate. PSH occurrence rate was high after SILC irrespective of the body weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…29,30 Our study failed to identify BMI as an adverse prognostic factor in the analysis of conversion and complication. The small number (23,11.5%) of obese patients (BMI .30 kg/m 2 ) in this study may be responsible for the statistical insignificance.…”
Section: Commentsmentioning
confidence: 76%
“…29,30 Our study failed to identify BMI as an adverse prognostic factor in the analysis of conversion and complication. The small number (23,11.5%) of obese patients (BMI .30 kg/m 2 ) in this study may be responsible for the statistical insignificance.…”
Section: Commentsmentioning
confidence: 76%
“…However, there seems to be varying degrees of difficulty in individual cases. In previous studies, height and BMI were reported as predictive factors for difficult SILC cases , with patients with a higher BMI or taller height had longer operative times. These effects are believed to be due to the longer distance to the target organ .…”
Section: Discussionmentioning
confidence: 93%
“…Previous papers have reported that BMI and height are predictive factors for prolonged operative duration in SILC patients . BMI is also associated with prolonged operative duration in CLC .…”
Section: Introductionmentioning
confidence: 91%
“…Seven patients (2.4%) had a trocar site hernia in our study, which is a comparable outcome with that of other studies. 19,20 All of these patients underwent hernia repair. In conclusion, transumbilical laparoscopic cholecystectomy can be performed in most patients with benign gallbladder The morbidity rates were not significantly different in whether cholecystitis or not in patients performed transumbilical laparoscopic cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%